The levelling-off of the secular trend of age at menarche among Italian girls - Piras, Gianluca Niccolò (Heliyon, 2020)
OBJECTIVE: The main aim of this study was to verify whether the secular trend stopped in Italy by comparing the results of a 1990–2000 birth cohort versus a 1980–1990 birth cohort of Italian young women. The results were used to speculate about age at menarche as adaptive response to non-genetic factors. METHODS: In 2016, a study was set on 413, 18-to-26 year-old women (1990–2000 birth cohort) attending two Italian Universities by web-based, self-reported questionnaires. Previously in 2000, a research including 3,783 high school female students (1980–1990 birth cohort) was led. The age at menarche distribution was performed by Kaplan-Meier analysis. The comparison between the findings of the two birth cohorts was performed by Wilcoxon sum-rank test. Mixed models analysis was applied to evaluate the effect of cohort and socio-economic status on age at menarche. RESULTS: 1990–2000 cohort's age at menarche median was 12.44y (95%CI 12.37; 12.59y). There was no significant difference with age at menarche of the previous cohort (p = 0.56). Consistently, the advance of age at menarche in comparison to the mothers' one was not significantly different between the two cohorts (-0.27y±0.10y vs -0.25y±0.03y, p = 0.33). The socio-economic level was not significantly associated with menarcheal age. CONCLUSIONS: The findings of this study confirm that, like in other developed countries, the advance of age at menarche has stopped in Italy, consistently with the stop of the improvement of socio-economic conditions. Further studies are needed to explore the differential effect of each non-genetic factor to outline future scenarios of human sexual maturation. TRIAL REGISTRATION: the Comitato Etico per la Sperimentazione Clinica (CESC) della Provincia di Padova of the Veneto Region (Italy), n°3993/U16/16.